2016
DOI: 10.1248/cpb.c15-01001
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of New Fluoroamodiaquine Analogues

Abstract: Malaria is one of the most important tropical diseases; the use of amodiaquine as a current chemotherapy in the treatment of malaria has shown some problems such as hepatotoxicity and agranulocytosis. In this work we present the rational design, synthesis, and biological evaluation (antimalarial activity, cytotoxicity and genotoxicity) of four new fluoroamodiaquine analogues. The results showed significant correlation between MolDock score and IC 50 values. The molecules 7b and c were the most active of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Similar strategy was adopted to synthesize fluoro-tebuquine analogues, but it resulted in diminished antimalarial activity compared to both AQ and tebuquine. , FAQ-4 (4′-fluoro- N - tert -butylamodiaquine) was later identified as a candidate for further development studies based on its activity profile (comparable to AQ), low toxicity, and an acceptable safety profile . More recently, Sousa et al reported the synthesis of FAQ-piperazines (Figure ), but these analogues exhibited a 16–106-fold reduction in antiplasmodial activity.…”
mentioning
confidence: 99%
“…Similar strategy was adopted to synthesize fluoro-tebuquine analogues, but it resulted in diminished antimalarial activity compared to both AQ and tebuquine. , FAQ-4 (4′-fluoro- N - tert -butylamodiaquine) was later identified as a candidate for further development studies based on its activity profile (comparable to AQ), low toxicity, and an acceptable safety profile . More recently, Sousa et al reported the synthesis of FAQ-piperazines (Figure ), but these analogues exhibited a 16–106-fold reduction in antiplasmodial activity.…”
mentioning
confidence: 99%
“…The interaction of the 2,8-trifluoromethyl bisquinoline with hematinf alls into an anticipated order of stability from singlecrystal diffraction studies with hydrogen-bonding [63] and covalent interactions dominating. [62,63] Hence, p···p interactions are often assumed to be the preferred orientation geometry [68] between drug and porphyrin but, to our knowledge, only one study compares the thermodynamics of ar ange of all three competing geometries, [62] which are essential for understanding antimalarialdrug action. [62,63] Hence, p···p interactions are often assumed to be the preferred orientation geometry [68] between drug and porphyrin but, to our knowledge, only one study compares the thermodynamics of ar ange of all three competing geometries, [62] which are essential for understanding antimalarialdrug action.…”
Section: Implicationsf or Effective Drug Designmentioning
confidence: 81%
“…[56b, 57-59] This evidencec ontradicts currently accepted models of antimalariald rug receptor interaction(s)b ecause if the interactions betweenr eceptor and ligand were based on frequency of appearancei ng raphical forms, then p···p depictions [22, 23, 34n, 67] are most common and axial, covalent,a nd coordination adducts [52, 56b, 57-61] are fewer in number.E dge-type interactions between drug and ligand are currently restricted to afew studies only. [62,63] Hence, p···p interactions are often assumed to be the preferred orientation geometry [68] between drug and porphyrin but, to our knowledge, only one study compares the thermodynamics of ar ange of all three competing geometries, [62] which are essential for understanding antimalarialdrug action.…”
Section: Implicationsf or Effective Drug Designmentioning
confidence: 99%
“…Among them, hybrid 55d (IC 50 : 94.3 nM) which was greater than twofolds more active than CQ and PQ (IC 50 : 213 and 643 nM, respectively) against CQR K1 strain, showed low cytotoxicity toward L6 cells (IC 50 : 17.6 μM), and SI was 186.6. The quinoline‐benzoimidazole 57 also displayed low cytotoxicity (CC 50 : >80 μM) toward VERO cells, as well as considerable activity (IC 50 : 800 nM) against CQR W2 strain, but it was less potent than AQ (IC 50 : 50 nM) …”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%